Maqasid Shariah and Organizational Performance: A Systematic Literature Review - Dasmadi, Dasmadi; Hadi, Syamsul; Junchu, Yang; Wahyuningtyas, Nabila; Wedadjati, Ratna Sesotya (Global Review of Islamic Economics and Business, 2024)
This study aims to develop a Pentagon-Shaped Ethical Measurement framework based on Maqasid Shariah to assess organizational performance. The research employs a systematic literature review approach, analyzing scholarly works related to Maqasid Shariah and organizational performance. The study identifies relevant research from 2015 to 2024 using databases such as Scopus. The study finds that Maqasid Shariah is a comprehensive ethical framework for evaluating organizational performance. The findings suggest that integrating Maqasid Shariah into performance measurement enhances organizational credibility, corporate governance, and long-term sustainability. This study provides a Pentagon-Shaped Ethical Measurement framework based on Maqasid Shariah for evaluating organizational performance. Unlike previous research that mainly focuses on financial performance. Organizations can utilize Maqasid Shariah principles to develop a more balanced and sustainable performance assessment model. The study highlights the role of Maqasid Shariah in promoting social welfare, economic justice, and ethical business practices. Adopting a multidimensional performance framework contributes to long-term economic sustainability, fair wealth distribution, and corporate social responsibility (CSR).